Generation of a vector suite for protein solubility screening - Correa, Agustin; Ortega, Claudia; Obal, Gonzalo; Alzari, Pedro; Vincentelli, Renaud; Oppezzo, Pablo J. (Frontiers in Microbiology, 2014)
Recombinant protein expression has become an invaluable tool for academic and biotechnological projects. With the use of high-throughput screening technologies for soluble protein production, uncountable target proteins were produced in a soluble and homogeneous state enabling the realization of further studies. Evaluation of hundreds conditions requires the use of high-throughput cloning and screening methods. Here we describe a new versatile vector suite dedicated to the expression improvement of recombinant proteins with solubility problems. This vector suite allows the parallel cloning of the same PCR product into the 12 different expression vectors evaluating protein expression under different promoter strength, different fusion tags as well as different solubility enhancer proteins. Additionally, we propose the use of a new fusion protein which appear to be a useful solubility enhancer. Overall in this work we propose an economic and useful vector suite to fast track the solubility of different recombinant proteins and we propose a new solubility enhancer protein that can be included in the evaluation of the expression of recombinant proteins that are insoluble in classical expression conditions.